Management of bridge with non-rigid connectors in cases with pier abutments: Penatalaksanaan gigi tiruan jembatan dengan konektor non-rigid pada pier abutment - Arrad Rambey; Ratna Sari Dewi (Makassar Dental Journal, 2023)
The type of denture bridge with pier abutments where there are stand-alone abutment teeth between the abutment terminals, requires the dentist to pay special attention. One crown is attached to a natural tooth, and the other crown is attached to a dental implant or other type of abutment, known as the pier abutment that can become a class I fulcrum if restored using a 5-unit bridge with rigid connectors, which can cause excessive force to be received by the retainer at the abutment terminal, leading to debonding of the retainer or even damage to the periodontal tissues of the abutment teeth. In addition to these problems, long-span bridges have a poor prognosis due to the mobility difference between the anterior and posterior teeth, which may cause excessive stress on the connector. The use of a non-rigid connector can overcome this problem, as it can be a stress breaker by allowing micro-movements in the connector. The design of semi-rigid bridge with pier abutments must consider factors such as span length, anticipated occlusal load, and mastication factor. Proper consideration of these factors ensures the safety and longevity of the bridge.